2020
DOI: 10.1177/1938965520981069
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and Individual Outcomes: The Mediating Role of Gratitude and Compassion at Work

Abstract: Corporate social responsibility (CSR) policies and activities are aimed at, executed for, and witnessed by individuals, yet CSR literature has long overlooked assessing CSR outcomes at the individual level. Previous CSR research has focused primarily on macro- and institutional-level outcomes. The current paper addresses this issue by analyzing the influence of CSR on a crucial stakeholder for hospitality organizations: their employees. Specifically, gratitude and compassion at work were tested as parallel med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 113 publications
2
44
0
Order By: Relevance
“…Future research in this area may help to explore any barriers to gratitude, and therefore may provide insight into the design of a gratitude intervention targeting specific groups in order to enhance greater wellbeing. This will complement the research that has found that gratitude at work is related to, among other positive outcomes, improved job satisfaction (e.g., [77]), reduced burnout (e.g., [78]), and increased organizational citizenship behaviours (e.g., [79]).…”
Section: Limitations and Future Directionssupporting
confidence: 56%
“…Future research in this area may help to explore any barriers to gratitude, and therefore may provide insight into the design of a gratitude intervention targeting specific groups in order to enhance greater wellbeing. This will complement the research that has found that gratitude at work is related to, among other positive outcomes, improved job satisfaction (e.g., [77]), reduced burnout (e.g., [78]), and increased organizational citizenship behaviours (e.g., [79]).…”
Section: Limitations and Future Directionssupporting
confidence: 56%
“…Thus, an inclusive CSR policy catering to both kinds of needs (Luo et al, 2020) results in enhanced job satisfaction (Kim et al, 2020), employee well-being (Guzzo et al, 2020;Su & Swanson, 2019), quality of work-life (Asante Boadi et al, 2019;Kim, Woo, et al, 2018), organizational commitment , OCB (Guzzo et al, 2020), and life satisfaction .…”
Section: Csr Researchmentioning
confidence: 99%
“…For instance, internal CSR meets lower‐order needs (i.e., physiological, economic, safety, affiliation, internal respect), while external CSR meets higher‐order personnel needs (i.e., external prestige/esteem, self‐actualization, transcendence) (Bibi et al, 2022; Kim et al, 2020). Thus, an inclusive CSR policy catering to both kinds of needs (Luo et al, 2020) results in enhanced job satisfaction (Kim et al, 2020), employee well‐being (Guzzo et al, 2020; Su & Swanson, 2019), quality of work‐life (Asante Boadi et al, 2019; Kim, Woo, et al, 2018), organizational commitment (Kim et al, 2017), OCB (Guzzo et al, 2020), and life satisfaction (Kim et al, 2017).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Our findings also provide empirical support for Fehr et al’s (2017) theoretical proposal that gratitude contributes to employee well-being. Although gratitude is known to play an important role in general well-being (Guzzo et al, 2020; Wood et al, 2010), only a handful of studies have explored the benefits of gratitude in terms of employee well-being (e.g., reduced depression, stress, burnout) (see Feng & Yin, 2021; Lau & Cheng, 2017; Lee et al, 2018; Lies et al, 2014). The comprehensive list of indicators in the current study addresses hedonic (LWB), eudaimonic (PWB), and context specific (WWB) aspects of employee well-being.…”
Section: Discussionmentioning
confidence: 99%